PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVMENT DIVISIONS DALAM MENINGKATKAN HASIL BELAJAR SISWA MELALUI LEMBAR KERJA SISWA PADA MATA PELAJARAN AKUNTANSI - Ma’ Sumarsih, (Pendidikan Ekonomi, 2012)
The purpose of this study si to know the teacher and the student activity to enhance the student learning outcomes and to discover students opinion in STAD cooperative learning through the worksheet in the trading companys adjustment journal lesson is X KU class of SMK Negeri 2 Nganjuk. This study is class action research that done in three cycles involves the planning, execution, observation and refection. The result shows that by applying the cooperative learning type STAD and Worksheet, the teacher do the activity successfully, whilst the student activity shows increase in each cycle. 2,5 in the first cycle which is good enough, in the second cycle is 3 means good, and 3,6 in the third cycle means very good. The learning outcomes also increased in each cycle that are 58,9, 76,7, 80 with the classical completeness 38,9%, 80,5% and 88,9% in each cycle consecutively. The students opinion about the method applies is good.